2014
DOI: 10.1530/erc-14-0088
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin receptor antagonist AT-001 synergizes with docetaxel in androgen-independent prostate xenografts

Abstract: Androgen hormones and the androgen receptor (AR) pathway are the main targets of anti-hormonal therapies for prostate cancer. However, resistance inevitably develops to treatments aimed at the AR pathway resulting in androgen-independent or hormone-refractory prostate cancer (HRPC). Therefore, there is a significant unmet need for new, non-androgen anti-hormonal strategies for the management of prostate cancer. We demonstrate that a relaxin hormone receptor antagonist, AT-001, an analog of human H2 relaxin, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…In contrast to the other members of the RXFP receptor family there have been few examples of peptides with antagonist properties at RXFP1. Peptide AT-001 (Neschadim et al, 2014) contains mutations of the B-chain residues R13 and R17 [that are essential for relaxin-like activity (Büllesbach et al, 1992)] to K13 and K17 (B-R13/17K relaxin). Initially, antagonism was demonstrated by lentiviral expression of the B-R13/17K relaxin, which decreased prostate cancer xenograft growth (Silvertown et al, 2007).…”
Section: Ligands That Act At Relaxin Family Peptide Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the other members of the RXFP receptor family there have been few examples of peptides with antagonist properties at RXFP1. Peptide AT-001 (Neschadim et al, 2014) contains mutations of the B-chain residues R13 and R17 [that are essential for relaxin-like activity (Büllesbach et al, 1992)] to K13 and K17 (B-R13/17K relaxin). Initially, antagonism was demonstrated by lentiviral expression of the B-R13/17K relaxin, which decreased prostate cancer xenograft growth (Silvertown et al, 2007).…”
Section: Ligands That Act At Relaxin Family Peptide Receptorsmentioning
confidence: 99%
“…In addition, medium from cells infected with the lentivirus showed human relaxin immunoreactivity and antagonized cAMP production from THP-1 cells in response to relaxin (Silvertown et al, 2007). However, a subsequent synthesis of the B-R13/17K peptide showed that although it competed for relaxin binding, the peptide was actually a partial agonist for cAMP production in cells overexpressing RXFP1 Neschadim et al, 2014) (Table 1). In cells expressing RXFP1 at lower (more physiologic) levels, B-R13/17K relaxin displayed functional antagonism, inhibited MCF-7 cell invasion, and prevented the inhibitory effect of relaxin on renal myofibroblast differentiation .…”
Section: Ligands That Act At Relaxin Family Peptide Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which relaxin contributes to tumor growth likely varies by tumor type, and, while it may involve contributions from various biological effects promoted by relaxin signaling, it clearly demonstrates in preclinical prostate cancer models to involve increased angiogenesis. In prostate cancer xenografts, analysis of tumor vasculature demonstrated that overexpression of relaxin in the tumor drives increased angiogenesis, characterized by the upregulation of various VEGF isoforms in tumors and manifesting in increased intratumoral microvessel density and microvessel cross‐sectional area, whereas antagonizing relaxin signaling in the tumor counteracts these effects . Overexpression of relaxin may also promote increased invasiveness and metastasis in prostate cancer, suggested by evidence from mouse models of human prostate cancer xenografts .…”
Section: The Role Of Relaxin In Cancermentioning
confidence: 99%
“…Recombinant expression of this relaxin receptor antagonist, termed ΔH2 relaxin, resulted in impaired prostate cancer tumor xenograft growth and angiogenesis . To this end we have recently developed a synthetic relaxin antagonist, AT‐001, for parenteral administration and have demonstrated that it is efficacious in impairing angiogenesis and reduces the growth of androgen‐independent human prostate cancer xenografts by up to 60%, in a model, where androgen‐targeted therapeutics are no longer effective. We have further demonstrated that AT‐001 synergizes with docetaxel chemotherapy to curb tumor growth by a mechanism that involves the downregulation of the hypoxia‐induced response in the treated tumors .…”
Section: Therapeutic Approaches Based On Antagonizing the Relaxin Sigmentioning
confidence: 99%